MEANS OF TRANSLATION OF JOURNALISTIC TEXTS AND THE PHENOMENON OF EQUIVALENCE IN WRITTEN TRANSLATION - Absamadova Munira Isroilovna (Journal of new century innovations, 2023)
This article discusses one of the most important and responsible areas of translation studies, the processes, problems and difficulties of translating journalistic texts. It is written about how important the translator's knowledge, vocabulary, and skills are when delivering the text directly to the reader while preserving the original. Newspaper text has a number of features that complicate the translator's work. When creating an adequate translation, the structure of the dictionary, the method of providing information, and its features require a lot of attention. Newspaper and news texts are special genre texts. Therefore, there are difficulties in translating them.